Susceptibility induced gray-white matter MRI contrast in the human brain - Langkammer, Christian; Krebs, Nikolaus; Goessler, Walter; Scheurer, Eva; Yen, Kathrin; Fazekas, Franz; Ropele, Stefan (NeuroImage, 2012)
MR phase images have shown significantly improved contrast between cortical gray and white matter regions compared to magnitude images obtained with gradient echo sequences. A variety of underlying biophysical mechanisms (including iron, blood, myelin content, macromolecular chemical exchange, and fiber orientation) have been suggested to account for this observation but assessing the individual contribution of these factors is limited in vivo. For a closer investigation of iron and myelin induced susceptibility changes, postmortem MRI of six human corpses (age range at death: 56-80years) was acquired in situ. Following autopsy, the iron concentrations in the frontal and occipital cortex as well as in white matter regions were chemically determined. The magnetization transfer ratio (MTR) was used as an indirect measure for myelin content. Susceptibility effects were assessed separately by determining R2* relaxation rates and quantitative phase shifts. Contributions of myelin and iron to local variations of the susceptibility were assessed by univariate and multivariate linear regression analysis. Mean iron concentration was lower in the frontal cortex than in frontal white matter (26±6 vs. 45±6mg/kg wet tissue) while an inverse relation was found in the occipital lobe (cortical gray matter: 41±10 vs. white matter: 34±10mg/kg wet tissue). Multiple regression analysis revealed iron and MTR as independent predictors of the effective transverse relaxation rate R2* but solely MTR was identified as source of MR phase contrast. R2* was correlated with iron concentrations in cortical gray matter only (r=0.42, p<0.05). In conclusion, MR phase contrast between cortical gray and white matter can be mainly attributed to variations in myelin content, but not to iron concentration. Both, myelin and iron impact the effective transverse relaxation rate R2* significantly. Magnitude contrast is limited because it only reflects the extent but not the direction of the susceptibility shift.
Available online 26 August 2011
Gesehen am 01.10.2018